Employment elasticity in India and the U.S., 1977 - 2011: A sectoral decomposition analysis - Basu Deepankar; Debarshi Das (University of Massachusetts, Department of Economics, 2015)
This paper analyses the phenomenon of jobless growth in India and the US through the lens of employment elasticity. Analytical results are derived for decompositions of both the level and change of aggregate employment elasticity in terms of sectoral elasticities, relative growth and employment shares. Estimates of these decompositions are presented with employment and output data from relevant sources for both economies. In India, the agricultural sector was the key determinant of both the level and change of aggregate elasticity till the early 2000s. In USA, services is the most important determinant of the level of, but manufacturing remains an important driver of changes in, aggregate employment elasticity.
Keywords: E2; E24; 330; employment; output; elasticity